Jawabanmu

Jawaban paling cerdas!
2014-04-16T15:47:48+07:00
X= -6,0
y=0,4

y-y1= x-x1
------=-------
y2-y1= x2-x1

y-0=x+6
-----=-------
4-0=0+6

y-0=x+6
------=-----
4=6

4x+24=6y-0
 -6y = -4x - 24 -0
 -6y = -4x-24
-------------------- : -2
3y= 2x +12

3y - 2x - 12= 0
jawabannya C

1 5 1
2014-04-16T16:01:58+07:00
Y-y1      X-X1
------- =  -------
y2-y1    X2-x1

y-0      X-(-6)
-----  = --------
4-0      0-(-6)

6y= 4(X+6)
6y= 4X + 24
------------------ :2
3y = 2X + 12

-2X + 3y -12 = 0

Semoga membantu :D